Pengaruh Jam Kerja Fleksibel dan Kompensasi terhadap Loyalitas Kerja Pengemudi Gojek di Bekasi Barat - Riswanda Ihza Rizky; Tyna Yunita; Tungga Buana Irfana; Hasanuddin Hasanuddin; Franciscus Dwikotjo Sri Sumantyo (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to find out, analyze and prove that employee work loyalty among Gojek drivers is partially influenced by flexible working hours and compensation. The research design uses quantitative research with a survey approach, the research population is 164 Gojek Drivers in the community in Bintara, West Bekasi. The sample measurement technique uses the formula Hair et al. (1998). With the accidental sampling method. The data collection technique used was a questionnaire. Data collection was carried out using a questionnaire distributed directly to 110 Gojek drivers in West Bekasi. The data was analyzed using SEM based on Partial Least Square with the help of Smart PLS Software.4. The analytical method used is outer model test, inner model test, hypothesis test. The research results show that (a) flexible working hours have a positive effect on work loyalty, (b) work rewards have a positive effect on work loyalty, (c) flexible work hours have an effect on compensation, (d) flexible work hours have an effect on work loyalty through the mediation of compensation.